Performance of The 3 Blades Horizontal Savonius Water Wheel With Variation of Angle Deflector - Wibowo, Daniel; Wihadi, Dwiseno; Martanto, Martanto; Tjendro, Tjendro; A, Ronny (SENATIK STT Adisutjipto, 2019)
In Indonesia the needs toward energy has been increasing. Therefore, eco-friendly renewable energy becomes an alternative power source. In relation to the idea, within the conduct of the experimental study the researcher designed a Savonius-type waterwheel with horizontal axis and the waterwheel was tested in the river stream. Then, within the design the researcher applied one waterflow regulator with the angle variation 30?, 45? and 60?. The study was conducted on river flow with a flow velocity of ± 0.6 m / s. the result is the addition of the deflector angle affects the ability to support the load, the maximum wheel efficiency(Cp) of 0.57.